All-solid-state quantum dot-sensitized solar cell from plastic crystal electrolyte. Issue 42 (10th May 2015) - Duan, Jialong; Tang, Qunwei; He, Benlin; Chen, Haiyan
<x xml:space="preserve">Abstract</x> A plastic crystal based solid-state electrolyte composing of plastic crystal succinonitrile and sodium sulfide (Na2S) is creatively synthesized by a simple blending approach.